REPRESENTASI ETOS KERJA MASYARAKAT BIMA DALAM BUDAYA KAPATU: KAJIAN ANTROPOLOGI SASTRA - Haris, Abdul; Hairun, Hairun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Kapatu is one of the oral literature that developed in the life people of Bima. As oral literature, Kapatu also represents various aspects of the social and cultural life of the Bima people, one of which is the work ethic. In essence, kapatu has been widely studied, but there are no researchers who focus on the problem of work ethic. Previous researchers examined kapu on elements of cultural structure, form and function, educational values, word forms and sound patterns, and language politeness. Based on this, the purpose of this study is to explain the form of the Bima people's work ethic in the Kapatu culture. This research is a qualitative type using a literary anthropological approach and descriptive method. Sources of research data came from two kapatu singers, Tarman N. Jafar and Khadijah who lived in Raba Kodo Village, Woha District, Bima Regency. Research data in the form of an array of kapatu taken from various titles, namely Dali, Teka Mpende, Kae, Lopi Peng, and Tambora. Data collection techniques using interactive techniques. The data analysis technique used descriptive analysis techniques. The results of this study are the work ethic of the Bima community through the Kapatu culture which represents a high work ethic. The indication of a high work ethic is because in their work the Bima community instills a humble attitude, does not get satisfied quickly, is disciplined, diligent, has a firm opinion, is brave in doing work, works hard, is responsible, patient in sailing, and does not give up easily work.